Macroeconomic conditions when young shape job peferences for life - Cotofan, Maria [Verfasser]; Cassar, Lea [Verfasser]; Dur, Robert [Verfasser]; Meier, Stephan [Verfasser] (My University, 2021)
“Preferences for monetary and non-monetary job attributes are important for understanding workers’ motivation and the organization of work. Little is known, however, about how those job preferences are formed. We study how macroeconomic conditions when young shape workers’ job preferences for life. Using variation in income-per-capita across US regions and over time since the 1920s, we find that job preferences vary in systematic ways with experienced macroeconomic conditions during young adulthood. Recessions create cohorts of workers who give higher priority to income, whereas booms make cohorts care more about job meaning, for the rest of their lives.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; I 2.3.2 Nordamerika; 370; 330; Berufseinmündung; Berufswahl; Einflussfaktor; Wirtschaftskrise; Einkommen; Historische Entwicklung; USA